NOVEL ONCE-DAILY EXTENDED-RELEASE TACROLIMUS VERSUS TWICE -DAILY TACROLIMUS IN DE NOVO KIDNEY TRANSPLANT RECIPIENTS DURING THE EARLY POSTTRANSPLANT PERIOD - Polatkan, Volkan; Ozdemir, Ebru; Erturk, Turker; Tatli, Emel; Berber, Ibrahim; Cakir, Ulkem; Yilmaz, Gulay (OXFORD UNIV PRESS, 2020)
57th ERA-EDTA Congress, ELECTR NETWORK, JUN 06-09, 2020